Toward sustainable and smart cities in Africa: A review and challenges - Dos-Santos, M. J. P. L. (2019)
The paper presents the main challenges to be overcoming in order in the future cities we have sustainable and smart cities in Africa. The analysis highlines confirm the existence of huge challenges, problems and restriction about social, economics, and environmental and political issues in Africa. This paper analysing the main constraints to urban development in the African Continent and confirms that smart cities only will be possible in Africa when the current problems of sustainable development (economic, social, environmental and political) are overcoming. However, the paper allows us understand why this is the first paper on the literature to address the topic of smart cities in Africa. Should be noted that in this continent there are at least two of the world's largest cities in terms of inhabitants and the growth of population rate of the African continent is about 2.5%. So, this is a world problem to minimize. The concern about the problems of sustainable development in this region and how to promote it towards sustainable cities competes to all and the follow way will affect all of the world sustainable development.